2015
DOI: 10.1016/j.lithos.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

What can we learn from melt inclusions in migmatites and granulites?

Abstract: With less than two decades of activity, research on melt inclusions (MI) in crystals from rocks that have undergone\ud crustal anatexis – migmatites and granulites – is a recent addition to crustal petrology and geochemistry.\ud Studies on this subject started with glassy inclusions in anatectic crustal enclaves in lavas, and then progressed\ud to regionally metamorphosed and partially melted crustal rocks, where melt inclusions are normally crystallized\ud into a cryptocrystalline aggregate (nanogranitoid).\u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
107
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 200 publications
13
107
1
1
Order By: Relevance
“…Recent studies have demonstrated that melt inclusions (MI) constitute a new and powerful tool to investigate crustal anatexis (Cesare 2008;Cesare et al 2009Cesare et al , 2011Cesare et al , 2015. Studies of MI in crustal anatectic enclaves found within peraluminous dacites of SE Spain have shown that these trapped droplets of melt, now solidified to glass due to rapid ascent and extrusion, can provide precise information on the composition of primary anatectic melts during, and on the mechanisms of, crustal anatexis (Cesare et al 1997(Cesare et al , 2003Acosta-Vigil et al 2007, 2012a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated that melt inclusions (MI) constitute a new and powerful tool to investigate crustal anatexis (Cesare 2008;Cesare et al 2009Cesare et al , 2011Cesare et al , 2015. Studies of MI in crustal anatectic enclaves found within peraluminous dacites of SE Spain have shown that these trapped droplets of melt, now solidified to glass due to rapid ascent and extrusion, can provide precise information on the composition of primary anatectic melts during, and on the mechanisms of, crustal anatexis (Cesare et al 1997(Cesare et al , 2003Acosta-Vigil et al 2007, 2012a.…”
Section: Introductionmentioning
confidence: 99%
“…A previous and fundamental step for the detailed studies on these crystallized MI has been the development and further refinement of appropriate methodologies to rehomogenize them successfully under high P, in order to prevent MI decrepitation and interaction with the host mineral and matrix rock (Bartoli et al 2013b; see also Malaspina et al 2006;Perchuk et al 2008). After application of this experimental methodology and subsequent analysis of several occurrences of nanogranites, Cesare et al (2015) have observed that the studied MI have bulk compositions varying from granitic to granodioritic, trondhjemitic and tonalitic, and hence they have renamed them as nanogranitoids. Barich et al (2014) have documented the presence of crystallized MI in Grt from strongly deformed, former high P granulitic migmatites overlying the Ronda peridotite slab, in the Betic Cordillera of S Spain (hereafter mineral abbreviations after Kretz 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Melt compositions trends in mesonorm diagrams plot over the anticipated areas, when compared with leucosome compositions from metasedimentary protoliths from Sawyer (2008). It also shows that the melt produced, after accumulation or extraction of 15 mol %, with garnet or cordierite stable in residual assemblage, has similar compositions to melt inclusions trapped in garnet or cordierite reported by Cesare et al (2015). This indicates that melt inclusions reflect not the composition of the "initial" melt, but the composition of the melt generated with a particular peritectic phase, as was proposed by Cesare et al, (2015).…”
Section: Melt and Residue Compositionssupporting
confidence: 69%
“…The melt compositions plotted in fig.11 show a superposition with the field from the compositions of the melt inclusions given by Cesare et al, (2015). This correlation indicates that melt produced with peritectic phases, either garnet or cordierite, from hydrate-breakdown melting, displays compositions close to those analysed from natural samples.…”
Section: Mesonorm Diagramsmentioning
confidence: 63%
See 1 more Smart Citation